Fluidoterapia transoperatória em cadelas submetidas à ovariohisterectomia videoassistida - Oliveira, Marília Teresa de (2016)
Anesthetic and surgical procedures alter the normal mechanisms of fluid homeostasis, making essential intraoperative fluid therapy. Thus, there is the concern of the establishment of an appropriate fluid for animals undergoing procedures that are rising in veterinary medicine, such as videosurgery. Considering the peculiarities of surgical video procedures and the lack of studies in small animals to evaluate the influence of different fluid rates for intraoperative this operative mode, the aim of this thesis was to conduct a literature review, highlighting the characteristics of this type of approach that can influence the intraoperative fluid therapy, and to verify the influence of restrictive pattern and liberal fluid in bitches submitted to video-assisted ovariohisterctomia (OVH). For the experimental study, 24 rigid animals were selected divided into three groups: G5 (5mL.kg-1.h-1), G10 (10 mL.kg-1.h-1) and G20 (20 mL.kg-1.h-1). HR were measured, f, ToC, SAP, DAP, MAP and CVP, as well as observation of acid-base balance through the blood pH measurement, PaO2, PaCO2, HCO3-, BE, Na+, K+, Cl- and SaO2. The evaluated parameters related to the urinary system were urea, creatinine, protein: creatinine taxes, urine specific gravity, urine output, urinary glucose. It was also analyzed blood count and blood lactate levels. Patients were evaluated preoperatively (M0) and monitored until 24 hours of surgery (M9). Blood pressure did not differ between groups. The G20 showed a more severe hypothermia M7 35,92oC ± 0.61 (p = 0.04) and less severe acidosis when compared to G5. At time of extubation, the G20 animals kept the urine output values in 2.17 mL.kg-1.h-1 ± 0.52, differing from the G5 (p <0.01). The lactate values differed in M8 (P = 0.03) between G5 (2.18 mmol/L ± 1.95) and G20 (0.78 mmol/L ± 0.15). There was no difference between groups in potassium levels, but the animals G20 showed lower values to reference for the species M6, M7 and M8. The rates of 10 or 20 mL.kg-1.h-1 were suitable for video-assisted OVH in bitches, provided they receive adequate thermal support intraoperatively and electrocardiographic monitoring to detect arrhythmias arising frames hypokalemia.